1997
DOI: 10.1088/0953-8984/9/20/008
|View full text |Cite
|
Sign up to set email alerts
|

Orientational and thermodynamic properties of rod - plate mixtures

Abstract: The molecular-statistical model of a fluid composed of rectangular parallelepipeds, that is continuous in translations and discrete in orientation distribution, is employed in calculations relating to regions corresponding to the stability of uniaxial and biaxial nematic phases in model mixtures of uniaxial rod-like and plate-like particles, interacting via steric repulsion. The calculations are performed taking into account three-particle correlations. It is shown that for fixed overall mole fraction, the val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 26 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…At the conclusions of his work, Alben mentions that a N + -N − phase separation might replace the B phase, but does not considers this possibility in his analysis. A similar phase behavior has later been obtained by other authors using different models [2,3,4,5]. They take into account the effect of having free (rather than restricted to a lattice) rotations and/or translations.…”
supporting
confidence: 78%
“…At the conclusions of his work, Alben mentions that a N + -N − phase separation might replace the B phase, but does not considers this possibility in his analysis. A similar phase behavior has later been obtained by other authors using different models [2,3,4,5]. They take into account the effect of having free (rather than restricted to a lattice) rotations and/or translations.…”
supporting
confidence: 78%
“…A second-order virial approximation [Eq. ( 54), without the last term] has been used to investigate the phase diagram of binary mixtures of rods and platelets [166,167]. It has been found that mixing rods and platelets can stabilize a biaxial nematic phase in which the symmetry axes of particles of different species point along mutually perpendicular directions.…”
Section: Psfrag Replacementsmentioning
confidence: 99%
“…In some cases qualitative differences in the types of phase behaviour are seen when compared with the full numerical solution particularly for mixtures (see the studies on mixtures of rod and disk-like particles [137][138][139][140]). The simple model of Zwanzig [88] (in which only the three cartesian orientations of the orientational distribution function are considered) have also found popular use owing to the tractable nature of the free energy [141][142][143][144][145][146][147][148][149][150][151][152][153][154]. As a final remark on the general use of trial functions, one should mention that in addition to being a useful ingredient in providing a representation of the thermodynamic properties of the isotropic-nematic transition, the Onsager, Gaussian and related trial functions have been used to analyse and describe the degree of orientational order determined experimentally [155][156][157][158][159][160].…”
mentioning
confidence: 99%